GENDER DIFFERENCE IN MATHEMATICAL LITERACY AND FACTOR THAT MAY AFFECT IT: PERBEDAAN GENDER DALAM LITERASI MATEMATIS DAN FAKTOR YANG MUNGKIN MEMENGARUHINYA - Qirom, Muhamad Syahidul; Turmudi; Juandi, Dadang (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2023)
Many research studies have shown that female students’ mathematical literacy is better than male students. However, the previous research viewed students’ mathematical literacy qualitatively. Maybe there are differences between the mathematical literacy of male and female students, but is it genuinely significant? Therefore, this research aimed to quantitatively investigate the differences in mathematical literacy between male and female students to provide empirical proof. In this study, 116 students at junior high school were the samples. The mathematical literacy test collected data about students’ mathematical literacy. The data were then analyzed using a comparison test of Mann-Whitney U to examine the hypotheses. The result showed no significant difference between male and female students’ mathematical literacy and whether, in general, and viewed from gender, students have low mathematical literacy. The factor that may affect the low and no significant difference between male and female students regarding mathematical literacy is teachers rarely provide students with mathematical literacy problems during the teaching and learning process.